Analyzing the Effect of Bureaucratic Leadership on Public Service Motivation and Job Performance - Dina Lesmana; Barkah Rosadi; Deni Hermana; Ran Liu; Alex Winarno (Universitas Muhammadiyah Malang, 2022)
Bureaucratic leadership in public institutions often gets a negative stigma due to a shift in understanding of bureaucracy in the public service system. This research aims to analyze the effect of bureaucratic leadership on public service motivation and job performance. A causal study through a questionnaire to employees at the sub-district level in Bandung randomly selected 245 employees. Data analysis using SEM procedure. The finding showed that bureaucratic leadership indicated by the encouragement of professionalism, distribution of power, coalitions, and leadership abilities in administrative matters could encourage motivation to provide services and ultimately improve service performance. Orientation to the public interest, self-sacrifice as a public servant, and interest in policy-making for the public interest as an indication of motivation to provide services mediate the influence of bureaucratic leadership on the performance of employees. Bureaucratic leadership influences employee performance either directly or through PSM. The theoretical implication is that the interaction between leaders and subordinates is a process of exchange and social learning for employees. The practical implication is the need to develop interactions between leaders and subordinates as a process of exchanging values and learning to improve employee motivation and performance.